Gendered Acquiescence and Resistance(s) to Coercive Sexual Practices Among Female Students at a Zimbabwean University. Issue 1 (June 2022) - Mukwidigwi, Tariro; Naidu, Maheshvari
High rates of sexual coercion among female students in institutions of higher education are a global concern. Although this phenomenon is universal, female university students' experiences and reactions to coercive sexual practices vary greatly due to differences in geo-socio-cultural milieus in universities. This study investigated the extent to which female students acquiesced or resisted gendered codes of sexual conduct during experiences of sexual coercion. Using mixed methodology, the study drew on the narratives of 341 female students and three key informants from a Zimbabwean university. The study's findings revealed that female students showed significant levels of acquiescence to gendered sexual norms and coercive sexual practices. This suggests that normative sexual practices embedded in university cultures subordinate women's sexuality, resulting in their vulnerability and acquiescence to coercive sexual practices. However, despite being positioned in a restrictive context which worked to instill and reproduce gendered norms of sexuality and acquiescence to coercive sexual practices, some female students demonstrated significant levels of "constrained" sexual agency, power and subjectivity. These students enacted embodied resistances and (re)negotiated gendered norms of sexuality in the form of negotiations, antagonistic reactions and (re)construction of dominant sexual practices and norms. Therefore, the study concludes that, while female university students conform to dominant sexual practices and norms, they also have the capacity to challenge them and actively resist and manage their experiences of sexual coercion